ASAS KEPATUHAN DALAM MENJALANKAN SISTEM PERJANJIAN KERJA WAKTU TERTENTU DI WILAYAH BOGOR - Iwan Wahyudi; martin Roestamy; endeh suhartini (Magister Hukum Sekolah Pascasarjana Unida, 2020)
The purpose of this study are: 1) To find out and analyze the principle of compliance in carrying out a Temporary Appointment Work Agreement system in the Bogor area. 2) To find out and analyze steps to improve the fate of workers in a Temporary Appointment Work Agreement system in the Bogor area. The research method used in this research is normative juridical research and sociological research. The results of this study are: 1) The principle of compliance in carrying out the system of Temporary Appointment Work Agreement in Bogor Regency and Bogor City, in practice there are still frequent violations, due to unclear rules regarding the application of a Temporary Appointment Work Agreement (PKWT). 2) Measures to improve the fate of PKWT system workers, in terms of legal structure refer to the form and position of legal institutions contained in the labour law system. For workers who are not in accordance with the laws and regulations, for the sake of law will change to PKWTT, which is changed to become permanent workers. The protection provided is in the form of rights and obligations as permanent workers in the form of protection of the rights to wages, occupational health, job security, severance pay, reward money for work tenure, and work replacement money. Legal culture (legal culture) includes the values contained in the community that underlies the applicable law in PKWT.